MATERNAL MORTALITY IS A KEY INDICATOR OF THE HEALTH SYSTEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The health status of any given country depends upon maternal and infant mortality rates, which play a crucial role in evaluating the country’s population health, quality of care, socioeconomic status, and poverty.